Aplicação De Fungos Filamentosos Na Β-Glicosilação Da Entacapona - LUSTOSA, Keyla Rejane Magno Dias (2011)
The study of bioconversion of biologically active compounds by microorganisms, mainly filamentous fungi and their possible glycosylated derivatives have been extensively explored and have brought promising results. Microbial models of animal metabolism, based on the similarity of the hepatic metabolism and microbial enzyme, became an alternative for the elucidation of metabolic routes of both drugs as well as new drug candidates. In this context, the objective of this study was to explore the ability of filamentous fungi to promote the bioconversion of entacapone and perform the identification, purification and characterization of derivatives formed. We selected eight filamentous fungi Absidia blakesleana ATCC 26617, Aspergillus candidus ATCC 1009, Beauveria bassiana ATCC 7159, Beauveria sp, Cunninghamella echinulata ATCC 9244, Cunninghamella echinulata ATCC 9245, Cunninghamella elegans ATCC 26169 and Rhizopus arrhizuz ATCC 11145, six of them proved to be effective in the metabolism of entacapone, Cunninghamella echinulata ATCC 9245 being the most promising. Were detected 5 different functionalized derivatives, one of which the majority was characterized by Nuclear Magnetic Resonance of Carbon (13C NMR) and Hydrogen (1H NMR), High-Performance Liquid Chromatography coupled to Mass Spectrometer (HPLC-MS/MS) and Infrared Spectroscopy (IR) as a β-glycosylated derivative of entacapone (E, Z): 4 hydroxy-5-nitrophenyl-3-O-(β)-D-glucopyranose-(E)-2-cyano-N, N-diethyl-3-acrylamide.